A Need Analysis on the Instructional Material Development of Speaking Skills for Secretarial Students - Didik Hariyadi Raharjo; Anis setiyanti; Fenti Sofiani (English Language in Focus (ELIF), 2021)
A professional secretary should be proficient in English communication, particularly in productive skills such as speaking and writing, to complete all of his duties. The research was aimed to determine the needs of the secretarial students in terms of speaking skills to meet the need for professional secretaries in today's business and industrial field. From March to August 2020, 30 secretarial students and 5 professional secretaries from Jakarta participated in this qualitative study. The research’s data was the students' needs that could be divided into target needs (necessities, lacks, wants) and learning needs based on Hutchinson and Waters's theory. The data was collected through observation, interviews, and questionnaires. The findings of the study indicated that the students should master the speaking skill needed to complete the secretarial tasks such a handling phone calls, facing a job interview, describing a product, making an appointment, making a hotel reservation, making a press release, running a business meeting, giving a presentation, winning a negotiation and many more. However, the students encountered a variety of speaking obstacles, including limited vocabulary and incorrect grammar. Furthermore, the students wanted to get a lot of interesting interactive materials that were wrapped in dialogues or monologues activities when learning to speak.